The Influence of Compensation and Work Motivation on Employee Performance through Employee Discipline - Anwar, Syaiful; Abrar, Unsul (PT. Riset Press International, 2023)
Work motivation is the starting point for achieving good employee performance because with good motivation, individuals are internally driven to take action, even without external factors. Therefore, work motivation is crucial in the process of achieving organizational goals. In other words, good motivation will have an impact on good employee performance, which will automatically contribute to the achievement of organizational goals. Work discipline refers to employees' adherence to organizational rules. With this discipline, employees will always strive to carry out their assigned tasks to the best of their ability. Therefore, the importance of employee discipline needs to be considered and improved. With disciplined employees, their performance in carrying out tasks and functions will be positively impacted. Thus, the researcher aims to determine the influence of compensation and work motivation on the dependent variable, which is individual employee performance, through employee discipline at PT. Urchindize, Madura Branch. The research objective is to determine the influence of the independent variables, namely motivation, on the dependent variable, which is employee performance, through employee discipline at PT. Urchindize, Madura Branch. The study sample consists of 80 employees. Path analysis is used for data analysis in this research. Based on the results of the analysis, it is found that compensation, motivation, and employee work discipline significantly influence employee performance, and motivation significantly influences performance through work discipline at PT. Urchindize, Madura Branch.